Anti-E alloimmunization in a pregnancy with a low antibody titer - K. Nakanishi; Y. Oishi; T. Miyamoto; E. Nakamura; K. Murakami; M. Ono; A. Nozawa; S. Kitamura; K. Sengoku (IMR Press, 2020)
Red blood cell alloimmunization during pregnancy causes hemolytic disease of the fetus and newborn. While alloimmunization in pregnancy is treatable with anti-D antibodies, management with other antibodies has not been studied. A 32-year-old woman had anti-E antibodies detected during pregnancy, but the titer was < 1 : 2. Her newborn was admitted to hospital because direct Coombs tests were positive. Low titers of maternal anti-E antibodies were found in the newborn. We performed phototherapy and administered intravenous immunoglobulin because the newborn showed early jaundice and hyperkalemia, which suggested hemolytic disease. After being discharged at 6 days of age, the baby was readmitted to hospital at 9 days because of recurrent jaundice and underwent phototherapy. The baby was later discharged without recurrence of jaundice. Low anti-E antibody titers in pregnancy can cause alloimmunization, which can be treated successfully. The potential risk of hemolytic disease should be considered in cases with such low titers.